Características de la mortalidad por COVID-19 durante y después de la pandemia en el Perú - Arrasco, Juan (2024)
Introduction. The COVID-19 emergency caused a pandemic with a great impact on mortality in Peru. Objective. To analyze the magnitude of mortality due to COVID-19 and identify some sociodemographic characteristics. Methods. A descriptive ecological study was carried out, analyzing data on deaths due to COVID-19 during the period 2020-2023, as well as publicly accessible socioeconomic and demographic indicators. The variables included in the study were: year of death, number of deaths, sex, age group, province of origin, natural region, macroregion, human development index (HDI), unmet basic needs (UBN) and population density. Results. 220,628 deaths due to COVID-19 were reported, of which 219,374 (99.43%) occurred during the pandemic and 1,254 (0.57%) in the post-pandemic period; The cumulative mortality rate was 6.76 deaths/1000 inhabitants. The COVID-19 death curve shows that between 2020-2023, five waves occurred, with the second wave having the highest mortality, followed by the first wave. Mortality predominated in men, older adults (69.77%) and adults (28.11%). The macroregion of Metropolitan Lima and Callao had the highest mortality rates with 9.36 deaths/1000 inhabitants. The provinces with the highest cumulative mortality rates were those located on the coast, in quintiles with less NBI, in quintiles with a higher HDI and in those provinces with a higher population density. Conclusions. The COVID-19 pandemic caused high mortality in Peru, being higher in males, older adults, from coastal cities, with higher population density and better socioeconomic indicators.